Basic Airway Management Classroom Course - Cedric Lefebvre; David Manthey; Casey Glass; Chadwick Miller; Mary Claire O'Brien; John Gaillard; James O'Neill (Association of American Medical Colleges, 2014)
Abstract Introduction Medical students, residents, faculty, and providers in specialties in which airway management is commonplace (i.e., emergency medicine, anesthesiology, critical care) are required to learn basic airway management information and skills. This course was developed as part of a comprehensive airway course for emergency medicine residents. Methods This basic airway classroom course consists of five independent didactic presentations, six small-group cases and one reference/reading list. Each didactic presentation is comprised of PowerPoint slides with original text, algorithms, and high-quality original images. These presentations cover the following topics: managing the airway, airway algorithms, rapid sequence intubation, pediatric airway management, ventilator management. Each presentation can be delivered independently, together, or in combination with other educational material. The small-group case files include documents for students and an answer key for the group facilitator/course instructor. Results We have used this curriculum both in its entirety and its individual components for the education of residents, medical students, and fellows at a large academic center emergency medicine residency training program over a 5-year period. It has been used effectively in the classroom setting and as an adjunct during an airway skills workshop. Surveys regarding the effectiveness of these learning tools have yielded positive results from learners. Discussion This course was developed to organize and standardize airway management education within our residency training program and it was used on a yearly basis. This work allows the instructor to use didactic presentations to deliver medical knowledge, to use case scenarios for small-group learning, or both. It can be used independently or in combination with other learning tools. It can be combined with an advanced airway management course and/or a skills lab. We dedicate 8-12 hours during one month every year to deliver this airway series, and all aspects of this curriculum have been very popular at our training program among learners and instructors alike.